The cancellation of ID cards in Colombia: a permeated damage to Colombian-Venezuelan migrants (Revista Investigación & praxis en CS Sociales, 2024)
The main objective of this research work is to demonstrate how the transgression of due process, defense, notification and publicity in the administrative act implemented by the National Registrar of Colombia for the cancellation of 4300 identification cards of Colombian immigrants maximizes the damage to the fundamental rights of the migrant population, children of Colombian nationals born in Venezuela, inhibiting the exercise of nationality through the materialization of the legal personality that arises from the legality of the identification document. The research was carried out by means of an exploratory methodology, using a documentary research that included data and information from legal sources, Colombian jurisprudence and other precepts issued by different governmental institutions. It is concluded that the absence of the notion of legality of the administrative act, together with the omission of the right to due process, defense, notification and publicity in the cancellation of the 4300 identity cards, affects the human rights of migrants, children of nationals born in Venezuela.
Keywords: migration; nationality; human rights; personal identification; migration policy; exclusion; vulnerability